The Relationship between the Implementation of Pregnant Women's Classes and Childbirth Anxiety - Novi Ariance; Anik Purwati; Raden Maria Veronika Widiatrilupi (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Anxiety before childbirth is a common psychological condition experienced by pregnant women, particularly those who are primigravida. Such anxiety can be influenced by various factors, including lack of knowledge, fear of pain, and uncertainty about the childbirth process. Prenatal classes are educational programs designed to improve pregnant women’s understanding, confidence, and readiness in facing labor. These classes typically provide information about pregnancy, childbirth, postpartum care, and newborn care. However, the extent to which prenatal classes effectively reduce anxiety before childbirth requires further investigation. This study aimed to determine the relationship between the implementation of prenatal classes and labor anxiety levels among pregnant women. A quantitative research design with a cross-sectional approach was used. The sample consisted of 30 pregnant women selected through purposive sampling. Data were collected using standardized anxiety questionnaires administered before and after participants attended prenatal classes. The data were analyzed using the Chi-Square statistical test with a significance level set at p < 0.05. The findings revealed a significant relationship between participation in prenatal classes and a reduction in labor anxiety, with a p-value = 0.000 (p < 0.05). These results indicate that prenatal classes can play an important role in preparing pregnant women mentally and emotionally for the childbirth process. The interactive education and supportive environment provided during these sessions help participants gain confidence and reduce fear. It is recommended that healthcare providers in health facilities continue to optimize the delivery of prenatal classes by incorporating more interactive methods and involving family members. Family support, in combination with structured prenatal education, can further enhance the effectiveness of these programs in reducing childbirth-related anxiety.